Effects of Grilling Of Beef and Chicken Satay on the Survival of Listeria Monocytogenes - Hanapi, Siti Zulaiha (2006)
The isolation and enumeration of heat-injured and non-injured of Listeria monocytogenes and other Listeria species was studied in samples of chicken (40 samples) and beef (50 samples) satay isolated from 3 different vendors around Kajang and Bangi, Selangor. Samples of chicken satay were grilled by the vendors for 180 seconds while beef satay was grilled for 270 seconds. The internal temperature obtained was 64+40C measured by probe. This resulted to reduce total viable count of chicken satay and beef satay by 3 log reduction. Three different methods namely, U.S. FDA (Canadian Version), Overlay method (Compendium Method for the Microbiological Examination of Food (1995) and Thin Agar Layer (TAL) (Kang and Fung, 1999) were evaluated for the recovery of Listeria species from raw and grilled chicken satay and beef satay. TAL method gives higher recovery rates compared with OV while U.S FDA method unable to allow the recovery of Listeria species in raw and grilled satay. Listeria species isolated from raw chicken and beef satay using TAL method were L. monocytogenes, L. innocua, L ivanovii and L. grayi, respectively. Similar Listeria species were also detected in grilled chicken and beef satay after grilled to 180 s.. L. welshimeri is the only species was isolated in raw beef satay. On contrary, in OV agar, three species namely, L. monocytogenes,, L. innocua and L. ivanovii were recovered in chicken satay with grilling time 150 seconds. However, prolonged heating to 180 seconds resulted in destruction of all Listeria species. Three different internal temperature (600C, 700C and 800C) and 3 different storage temperature (40C, 300C and –200C) were studied in chicken satay inoculated with L. monocytogenes (~106-7 CFU/g). The population of L. monocytogenes increased rapidly on chicken satay stored at 300C for 24 hours. L. monocytogenes was also shown the ability to survive at refrigeration temperature for up to 7 days. In temperature storage at –200C, the population of L. monocytogenes remained 14 days only. A study of hemolysin gene using specific Polymerase Chain Reaction (PCR) showed that L. monocytogenes was found resistance to internal temperature of 60 and 700C but not at 800C. Results clearly demonstrated that the detection and enumeration of injured Listeria species was influenced by the medium used for the isolation. Microorganism that have been treated with a sub-lethal stress are considered injured if they fail to grow and produce colonies when they are plated on agar media containing selective agents. The interpretation results found that the pattern of growth of Listeria in satay (raw and grilled) was strongly influenced by the storage and internal grilling temperatures. Higher heating temperature resulted in destruction of L. monocytogenes in grilled satay.